2003
DOI: 10.1111/j.1752-1688.2003.tb04432.x
|View full text |Cite
|
Sign up to set email alerts
|

SIMULATING HYDROLOGIC AND WATER QUALITY IMPACTS IN AN URBANIZING WATERSHED1

Abstract: The Hydrologic Simulation Program‐Fortran (HSPF) was calibrated and used to assess the future effects of various land development scenarios on water quality in the Polecat Creek watershed in Caroline County, Virginia. Model parameters related to hydrology and water quality were calibrated and validated using observed stream flow and water quality data collected at the watershed outlet and the outlets of two sub water sheds. Using the county's Comprehensive Plan, land use scenarios were developed by taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 9 publications
5
24
0
Order By: Relevance
“…Rising urbanization would lead to an increase in the extent of impervious lands, resulting in more severe flood events. These results are comparable with those from Im et al [39] in the Polecat Creek watershed in Caroline County, Virginia, and Hejazi and Markus [40] in Northeastern Illinois. The increase in flood peaks due to urban expansion is also discussed by Du et al [11], wherein they revealed that impervious land in the Qinhuai River basin, China, will increase from 3% to 31% by 2018, resulting in an increase in daily peak discharge of approximately 14%.…”
Section: The Effects Of Land-use Changes On Discharge and Peak Flowsupporting
confidence: 82%
“…Rising urbanization would lead to an increase in the extent of impervious lands, resulting in more severe flood events. These results are comparable with those from Im et al [39] in the Polecat Creek watershed in Caroline County, Virginia, and Hejazi and Markus [40] in Northeastern Illinois. The increase in flood peaks due to urban expansion is also discussed by Du et al [11], wherein they revealed that impervious land in the Qinhuai River basin, China, will increase from 3% to 31% by 2018, resulting in an increase in daily peak discharge of approximately 14%.…”
Section: The Effects Of Land-use Changes On Discharge and Peak Flowsupporting
confidence: 82%
“…HSPF has been widely applied in watersheds with diverse geographic characteristics and is commonly used to characterize watershed processes and stream hydrology (Im et al 2003;Ribarova et al 2008) to evaluate the hydrologic and water quality impacts of land-use changes (Hunter and Walton 2008), and to explore effects of climate change (Albek et al 2004). …”
Section: Modeling Approachmentioning
confidence: 99%
“…Similarly, livestock grazing and dairies may increase the presence of fecal bacteria (Bach et al 2002), provoke erosion problems, and increase stream turbidity (Strunk 2003). Conversion of agricultural areas, forests, grass, and wetlands to urban areas leads to large proportional increases in land imperviousness in the form of roofs, sidewalks, roads, parking lots, and turf grass that can dramatically alter the natural hydrologic condition within a watershed (Im et al 2003). The outcome of this alteration is typically reflected in increases in the volume and rate of surface runoff and decreases in groundwater recharge and base flow.…”
Section: Introductionmentioning
confidence: 99%
“…The bibliography provided by developers contains more than 300 entries. The performance of SWAT and HSPF were compared by several authors (Im et al, 2003;Nasr et al, 2004;Saleh and Du, 2004;Sigh, et al, 2004), where both models were applied to the same watersheds. In these studies, both models produced comparable results; however HSPF produced slightly more accurate results in river discharges, whereas SWAT was better in reproducing the nutrient loads.…”
Section: Watershed Modelsmentioning
confidence: 99%